25-Hydroxy Vitamin D, Vitamin D Receptor and Toll-like Receptor 2 Polymorphisms in Spinal Tuberculosis: A Case-Control Study. Issue 17 (April 2016) - Panwar, Ajay; Garg, Ravindra Kumar; Malhotra, Hardeep Singh; Jain, Amita; Singh, Arvind Kumar; Prakash, Shantanu; Kumar, Neeraj; Garg, Rajiv; Mahdi, Abbas Ali; Verma, Rajesh; Sharma, Praveen Kumar
Abstract : Abstract: Vitamin D deficiency and vitamin D receptor (VDR) gene abnormalities confer susceptibility to tuberculosis. Toll-like receptors (TLRs), such asTLR-2, are also important mediators of inflammatory response against Mycobacterium tuberculosis . We evaluated serum vitamin D, and VDR and TLR-2 gene polymorphisms in patients with spinal tuberculosis. This study comprised of 3 groups: spinal tuberculosis, pulmonary tuberculosis, and controls (each with 106 subjects). Enzyme-linked immunosorbent assay was used to measure vitamin D levels, and polymerase chain reaction-sequencing method was used to analyze VDR and TLR-2 gene polymorphisms. Patients were followed up for 6 months. Vitamin D deficiency was significantly more prevalent in patients with spinal tuberculosis ( P < 0.001) and pulmonary tuberculosis ( P = 0.011), versus controls. The heterozygous and mutant genotypes of VDR TaqI gene were significantly associated with spinal tuberculosis ( P < 0.001; odds ratio [OR] 4.74 [2.45–9.18]) and pulmonary tuberculosis ( P < 0.001; OR 3.52 [1.80–6.88]) when compared with controls. The heterozygous and mutant variants of VDR ApaI gene were significantly more common in patients with spinal tuberculosis in comparison with patients with pulmonary tuberculosis ( P < 0.001; OR 2.90 [1.65–5.10]) and controls ( P < 0.001; OR 6.56 [3.41–12.61]). We did not observe any significantly different results for TLR-2 gene polymorphisms. Vitamin D deficiency, VDR, and TLR-2 polymorphisms did not affect the 6-month disability. Vitamin D deficiency and VDR gene polymorphisms are significantly more prevalent in people with pulmonary and spinal tuberculosis. They may, in isolation or collectively, confer susceptibility to pulmonary and spinal tuberculosis.